2012
DOI: 10.1111/fwb.12003
|View full text |Cite
|
Sign up to set email alerts
|

Estimating migratory fish distribution from altitude and basin area: a case study in a large Neotropical river

Abstract: Summary 1. The objective of this study was to identify longitudinal distribution patterns of large migratory fish species in the Uruguay River basin, southern Brazil, and construct statistical distribution models for Salminus brasiliensis, Prochilodus lineatus, Leporinus obtusidens and Pseudoplatystoma corruscans. 2. The sampling programme resulted in 202 interviews with old residents and fishermen at 167 different sampling sites in the major rivers of the basin. Interviewees were asked whether these fish spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 14 publications
2
7
1
Order By: Relevance
“…Our results fitted very well with previous research that showed altitude considerably affects fish distribution in aquatic ecosystems (Amarasinghe & Welcomme 2002;Yoon et al 2011;Barradas et al 2012;Stojkovic et al 2013). However, altitude is a complex variable: it can cause direct and indirect effects on fish distribution.…”
Section: Potential Determinants Of Lake Fish Diversity and Assemblagessupporting
confidence: 91%
“…Our results fitted very well with previous research that showed altitude considerably affects fish distribution in aquatic ecosystems (Amarasinghe & Welcomme 2002;Yoon et al 2011;Barradas et al 2012;Stojkovic et al 2013). However, altitude is a complex variable: it can cause direct and indirect effects on fish distribution.…”
Section: Potential Determinants Of Lake Fish Diversity and Assemblagessupporting
confidence: 91%
“…Despite the intense effort to map and organize the occurrences of aquatic biota in databases, the challenge is related to the unavailability of detailed environmental layers, especially for aquatic environments in small scales. However, successful examples of inference concerning distributional patterns with relative few predictors are already described for freshwater fish (Alves and Fontoura, 2009;Barradas et al, 2012) by using LOGIT functions, showing that satisfactory predictions could be achieved with relatively few key environmental predictors.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, altitude could generate direct barrier effects on distribution and life history traits of organisms, e.g. limit the colonization and speciation of fish (Yoon et al, 2011;Barradas et al, 2012;Stojkovic et al, 2013). As a complex variable, altitude can also bring indirect impacts on fish assemblages due to collinearity with climatic factors (Brucet et al, 2013).…”
Section: Prediction and Determinants Of Fish Species Assemblages In Cmentioning
confidence: 99%